2021
DOI: 10.1088/1361-6579/abf886
|View full text |Cite
|
Sign up to set email alerts
|

A novel calibration for L-shell x-ray fluorescence measurements of bone lead concentration using the strontium Kβ/Kα ratio

Abstract: Objective. Lead (Pb) is a well-known toxic element. In vivo bone Pb concentration measurement is a long-term exposure metric complementary to blood Pb concentration measurement which is a metric of recent exposure. In vivo human tibia bone Pb measurements using Pb K-shell or L-shell x-ray fluorescence (KXRF or LXRF) emissions were developed in the 1980s. KXRF bone Pb measurements using Cd-109 gamma rays and coherent-to-fluorescence ratio to account for differences between phantom and in vivo measurements, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…The experimental equipment was presented in our previous publications [59][60][61]. For clarity, the main experimental equipment is described in this section.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental equipment was presented in our previous publications [59][60][61]. For clarity, the main experimental equipment is described in this section.…”
Section: Methodsmentioning
confidence: 99%
“…In both cases, the sample was positioned at 15 mm from the PXL end as indicated in Figure 1a. At this position, the lateral size of the X-ray beam expressed as FWHM was 1.7 mm [60]. The XRF procedure titled the optimal grazing-incidence position (OGIP) [58][59][60], was applied to both samples.…”
Section: Xrf Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the study demonstrated the potential of the system for large scale population studies though further consideration for accuracy and precision is still required, especially at lower Pb concentrations. A paper by Gherase et al 129 described developments for the calibration of L-shell KXRF spectrometry for the determination of in vivo Pb in bone. In this work, the effect of soft tissue thickness was addressed with bone phantoms doped with various levels of Pb and a fixed amount of Sr and coated in polyoxymethylene, resin and wax to mimic the soft tissue at four different thicknesses between 1–4 mm.…”
Section: Progress With Analytical Techniquesmentioning
confidence: 99%